Daughter of Troy : a novel of history, valor, and love - Franklin, Sarah B., 1933-2018 (Avon Books, 1998)
Two heroes of ancient Greece fight over a beautiful widow during the Trojan War. She is Queen Briseis, enslaved by Prince Achilles after he conquered her kingdom, killing her husband, but King Agamemnon also covets her. Fortunately for Achilles she has fallen in love with him. A debut in fiction.